Photo-modulable molecular transport junctions based on organometallic molecular wires - Meng, Fanben (2013)
Photo-modulable molecular transport junctions are developed via on-wire lithography-fabricated nanogaps functionalized with a dithienylethene unit bearing two ruthenium fragments. A reversible and repeatable bi-state conductive switching upon alternate irradiation of UV and visible light can be distinctly observed. Theoretical calculations further suggest that bi-directional isomerization is due to the ruthenium moieties that modulate judiciously the electronic coupling between the photochromic part and the metal electrodes, and that the differences in electronic structure between the two isomers (open and closed states) are responsible for conductivity switching.